Size Composition of Fish By-Catch Species from Industrial Shrimp Trawl Fishery in Nigerian Coastal Waters - I O Taiwo; O A Olopade (Marine Science Department Diponegoro University, 2017)
Fish species composition of by-catch in the industrial shrimp trawl fishery in Nigeria was investigated with the Sciaenidae family being the most prevalent by-catch fish species. In order of prevalence Pseudolithus elongatus with a mean weight and length of 15.28g and 86.39mm, respectively and Pseudolithus typus (n= 102) having an average weight of 18.76g and mean length of 88.01mm. Other fish by-catch species include Pseudolithus senegalensis (n= 99, mean weigh = 15.49g, mean length= 88.60mm); Galeoides decadactylus (n= 59, mean weight= 15.26g, mean length= 87.66mm); Pteroscion peli (n= 48, mean weight= 16.05g, mean length = 88.23mm); Drepane africana (n= 33, mean weight= 13.29g, mean length= 45.73mm) and Cynoglossus senegalensis (n= 11, mean weight= 21.78g, mean length = 86.45mm). Despite the small number of Cynoglossus senegalensis, it had the highest weight contribution to the by-catch. Significant (P<0.01) relationship exists between weight and length of fish species. The adjusted R2 of the parameters indicated that 19.4% of the weight gained is accounted for by increase in length of Pseudolithus elongatus; 1.7% in Pseudolithus typus; 31.7% in Pseudolithus senegalensis; 13.7% in Galeoides decadactylus; 7.8% in Pteroscion peli; 57.4% in Drepane Africana; and 48.9% in Cynoglossus senegalensis. The by-catch associated with shrimp trawls should be properly monitored and controlled to reduce the quantity of non-target fish species in their catch. Also, the use of diamond-shaped 44mm mesh size for shrimp should be encouraged or made mandatory for fishers to reduce fish by-catch. Keywords: Shrimp, by-catch, fishery, weight